Manfaat Teknologi Maklumat dalam Industri Kecil dan Sederhana di Negeri Kedah D.A - Erwin, Hj. Azlir (1996)
The objective of this study is to determine the benefits derived from using information technology (IT) in the small and medium scale industries (SMI) in Kedah Darul Aman. The benefits which have been ascertained are tangible benefits, intangible benefits and management satisfaction with the IT usage in the organization. Only manufacturing companies are included in this study. The survey research method was used with disproportionate stratified random sampling. Thirty six companies were eligible to be used as the research sample. The industrial sector were divided into six categories, namely food & beverage, electric & electronics, furniture, plastics, basic & fabricated metal, and machines & tools. Twelve hypotheses were generated to determine the benefits of IT and their relationship with the usage of IT. These hypotheses were tested using descriptive and inferential statistical methods. The result from those tests showed the main benefits of IT are reducing error, improving staff productivity, improving customer service, providing better management information, providing better management control and increasing management productivity. IT was found to be widely used by bumiputera SMI. However, only 38.97% of SMI managers used computers. The most popular hardware is IBM personal computer or other compatible brands. The most used software is word processing followed by accounting packages. The business function’s most often used IT are the marketing and production functions while the administration functions are the financial & accounting and the general office.